Discovery of Eremiobacterota with nifH homologues in tundra soil - Pessi, Igor, S; Delmont, Tom, O; Zehr, Jonathan, P; Hultman, Jenni (Environmental Microbiology Reports, 2024)
International audience We describe the genome of an Eremiobacterota population from tundra soil that contains the minimal set of nif genes needed to fix atmospheric N 2 . This putative diazotroph population, which we name Candidatus Lamibacter sapmiensis, links for the first time Eremiobacterota and N 2 fixation. The integrity of the genome and its nif genes are well supported by both environmental and taxonomic signals. Ca. Lamibacter sapmiensis contains three nifH homologues and the complementary set of nifDKENB genes that are needed to assemble a functional nitrogenase. The putative diazotrophic role of Ca. Lamibacter sapmiensis is supported by the presence of genes that regulate N 2 fixation and other genes involved in downstream processes such as ammonia assimilation. Similar to other Eremiobacterota, Ca. Lamibacter sapmiensis encodes the potential for atmospheric chemosynthesis via CO 2 fixation coupled with H 2 and CO oxidation. Interestingly, the presence of a N 2 O reductase indicates that this population could play a role as a N 2 O sink in tundra soils. Due to the lack of activity data, it remains uncertain if Ca. Lamibacter sapmiensis is able to assemble a functional nitrogenase and participate in N 2 fixation. Confirmation of this ability would be a testament to the great metabolic versatility of Eremiobacterota, which appears to underlie their ecological success in cold and oligotrophic environments.